What Kind of Person Should an Education System Raise? A Survey of Teachers’ Views in Turkey (Journal of Education and Educational Development, 2020)
This study aims to find answers to the question: What kind of person should the Turkish education system raise? To evaluate the participants’ responses thoroughly, the phenomenology method has been used. The study group includes 185 teachers and school administrators working in Sivas city centre. To reach out to more participants, the data have been obtained by a survey developed by the researcher. Four categories, academic, social, individual, and ethical, have been identified as a result of data analysed with content analysis. The data have been presented according to the variables of school type and positions. According to the findings, it has been found out that teachers’ order of preference about the kind of person to be raised is individual, academic, ethical, and social characteristics; administrators’ order of preference is academic, individual, ethical, and social characteristics. Sentences have been formed about the kind of a person to be raised by the variables of school types and positions in the study. In this regard, considering participants’ priorities, common phrases have been brought out to be ‘having critical thinking, ethical, national and moral values, and love of country and nation’.